Mirvetuximab Soravtansine in solid tumors: A systematic review and meta-analysis. - Shamsnur Rehim; Shuang Yuan; Hongjing Wang (PLoS ONE)
Background Mirvetuximab Soravtansine (MIRV) is a promising antibody‒drug conjugate (ADC) that targets folate receptor alpha (FRα), which is overexpressed in several types of solid tumors. In November 2022, MIRV was approved in the USA for the treatment of adult patients with FRα-positive, platinum-resistant epithelial ovarian, fallopian tube or primary peritoneal cancer who received 1-3 prior systemic treatment regimens. Therefore, high-quality evidence for its efficacy and safety in different cancers is urgently needed. Methods A systematic search (e.g., PubMed, Embase, Web Of Science, Cochrane Library) was conducted to identify all relevant clinical trials of MIRV alone or in combination with chemo- and/or target-therapies in solid tumors. The primary end-point was median progression-free survival (mPFS). The secondary endpoints were the Objective response rate (ORR) and adverse effects (AEs). A random-effects model was applied. Results The study included nine research studies with a total of 682 patients. The pooled mPFS and pooled ORR were 6.70 months (95% CI 4.54-8.86, I2 = 96.21%) and 36% (95% CI: 28% to 44%, I2 = 76.79%), respectively. Significant differences were observed among intervention regimens and response to platinum. The pooled mPFS of MIRV monotherapy and MIRV+ Bevacizumab (BEV) combined therapy was 4.28 (95% CI 3.90-4.65, I2 = 0.00%) and 7.78 (95% CI 6.62-8.95, I2 = 0.00%), respectively. The pooled ORRs of MIRV monotherapy and MIRV+BEV combined therapy were 25% (95% CI 21%-29%, I2 = 25.20%) and 43% (95% CI 36%-50%, I2 = 0.01%), respectively. The pooled ORRs of the platinum-sensitive, platinum-resistant groups were 59% (95% CI 36%-81%, I2 = 61.88%), 33% (95% CI 25%-40%, I2 = 69.73%), respectively. In addition, we conducted supplementary subgroup analyses to explore the influence of FRα receptor expression levels and the number of prior treatments on treatment outcomes. The most common adverse effects were blurred vision (45.20%), nausea (40.13%), diarrhea (39.52%), fatigue (33.84%) and keratopathy (31.20%). Conclusions MIRV has significant therapeutic effects in solid tumors, especially when combined with BEV. In platinum-tolerant tumors, the efficacy of MIRV is also considerable. Overall, MIRV is relatively safe in solid tumors, and adverse reactions are relatively rare and mild.